Negotiating the GST Minefield: The Discourse of Nation Building in GST News Reports - Ong, Cheng Teik; Abdul Rahim, Hajar (Pusat Pengajian Ilmu Kemanusiaan, 2019)
The exercise of power through language instead of physical coercion is commonly employed by governments to persuade and convince people about certain policies and issues. This study contextualises such sophisticated operationalisation of power through the promotion of the GST discourse by the former Barisan Nasional (BN) government in curated GST news articles on the previous BN government’s GST website GST Malaysian Info that published positive GST news articles by the BN friendly mainstream media. Among the various discourses subsumed under the nodal GST discourse, this paper will focus on the discourse of nation building in the selected news articles and how it is linguistically realised. Used interchangeably, nation-building and national development refers to the improvement of a country and her people in all aspects of life such as economy, culture and an equitable distribution of benefits and wealth (The United Nations Declaration of the Right to Development, 1986). Over the years, nation building in Malaysia hinges on carefully formulated economic policies and plans by the government to chart the development of the country’s economy, including the implementation of the GST.